Impact of Flipped Classroom on Elementary Students' Creative Thinking in the Merdeka Curriculum - Regita Pramesty Kartika; Akhtim Wahyuni (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2023)
Creative thinking ability is the ability to create an idea to solve a problem. SDN Glagaharum is one of the elementary schools that has a relatively low creative thinking ability, this can be seen from the ability of students to understand the material in the Merdeka curriculum. To address this, researchers explored the use of the flipped classroom learning model. This study was conducted with the aim of knowing how the flipped classroom model affects the basic creative thinking skills of school students in implementing the Merdeka curriculum. Employing a quantitative experiment, the Posttest Only Control Group Design was employed with a population of 40 fourth-grade students from SDN Glagaharum. Two samples, IV-A (experiment class with 20 students) and IV-B (control class with 20 students), were utilized. Data analysis included normality and homogeneity tests, along with paired sample t-test conducted in SPSS 26. The findings revealed that the flipped classroom learning model had a significant effect on the creative thinking ability of fourth-grade students at SDN Glagaharum within the context of the Merdeka curriculum.